Faktor-Faktor yang Berhubungan dengan Perilaku Terkait Adab Makan Menurut Qur’an dan Sunnah pada Dewasa Muslim - Yustiyani, Yustiyani; Almagribi, Ahmad Bilal (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
The purpose of this study was to determine the factors factors associated with knowledge, attitudes and behavior of the application of eating manners according to the Qur'an and Sunnah. This research is a quantitative study using a cross sectional study design. The inclusion criteria of the subject were adult moslem aged 19-59 years old, reside in urban area, and able to read and write. The subject were 111 education staff at the UIN Syarif Hidayatullah Jakarta, South Tangerang City, Indonesia. The data collection was conducted by filling out an online questionnaire using Google Form application. Results shows that most of the respondents had a fairly good level of knowledge (75.7%), attitudes (53.2%), and behavior (55.9%) regarding eating etiquette according to the Qur’an and Sunnah. The level of education was related to the knowledge (p-value = 0.027), attitudes (p-value = 0.005), and behavior (p-value = 0.023) of respondents’ eating etiquette. Marital status was related to respondents' attitudes on eating etiquette (p-value = 0.012). There is no relationship between respondents' knowledge and attitudes with their eating etiquette practice (p-value > 0.05). The university is recommended to provide education regarding eating etiquette according to the Qur’an and Sunnah, especially to employees with lower education level.